2014
DOI: 10.1186/1745-6215-15-354
|View full text |Cite
|
Sign up to set email alerts
|

The Individualized Diet and Exercise Adherence Pilot Trial (IDEA-P) in prostate cancer patients undergoing androgen deprivation therapy: study protocol for a randomized controlled trial

Abstract: BackgroundAndrogen deprivation therapy (ADT) is the foundation of treatment for men with metastatic prostate cancer and is now frequently incorporated into multimodality strategies for the curative treatment of locally advanced prostate cancer. Nevertheless, the catabolic effects of ADT result in meaningful adverse effects on physiological and quality of life outcomes, which may, in turn, increase the risk of functional decline, frailty, cardiovascular disease, and metabolic syndrome. Recent evidence demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…Only two randomized trials looked at this important facet; one showed a reduction in C-reactive protein after 12 weeks of exercise, but no differences in systolic blood pressure, blood glucose, or lipids was demonstrated. 75 A further prospective randomized trial of dietary and exercise intervention is underway, 76 but while these important studies may yield benefits to prostate cancer patients, they are unlikely to be able to demonstrate whether such interventions are capable of ameliorating the risks associated with ADT. 74 77 What is clear is that in the general population, cardiac rehabilitation programs that primarily utilize exercise produce compelling and consistent clinical results in men with preexisting cardiovascular disease.…”
Section: Basic Physiologymentioning
confidence: 99%
“…Only two randomized trials looked at this important facet; one showed a reduction in C-reactive protein after 12 weeks of exercise, but no differences in systolic blood pressure, blood glucose, or lipids was demonstrated. 75 A further prospective randomized trial of dietary and exercise intervention is underway, 76 but while these important studies may yield benefits to prostate cancer patients, they are unlikely to be able to demonstrate whether such interventions are capable of ameliorating the risks associated with ADT. 74 77 What is clear is that in the general population, cardiac rehabilitation programs that primarily utilize exercise produce compelling and consistent clinical results in men with preexisting cardiovascular disease.…”
Section: Basic Physiologymentioning
confidence: 99%
“…The Mindfulness in Motion and the Dietary counselling portions of the intervention have both been previously validated in research studies. 24 , 26 , 68 However, this was the first time they have been combined to target a unique population of cancer survivors in order to improve lifestyle behaviors and potentially relevant health outcomes. Most traditional approaches to weight loss (increasing PA and improving diet) may be seen as particularly challenging for women who are dealing with a diagnosis of cancer, obesity, and trying to manage multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Study support was provided by National Cancer Institute Grant #R03 CA16296901 (Trial Registration: NCT02050906 Registered; 24 January 2014). Detailed reports of the study design, trial procedures, and interventions have been published previously 34–36 . A brief summary of the relevant methods and procedures is provided here.…”
Section: Methodsmentioning
confidence: 99%